(untitled) (PJDOL, 2023)
Education is one of most important aspect which converts human resource into a productive resource. Qualitative education is a barometer for social, cultural, economical and overall development. Recent development of ICT and its global acceptance has created new door for Education. E-learning is still very emerging field which may be beneficial for its human resource, if use properly. Development of Internet technology has opened up new methods for delivery of education. E-learning is another way of teaching and learning. It comprises of Instructions delivered through electronic media including the Internet, Intranet, Extranet, Satellite broadcasts, audio/video tapes, interactive television and CD-ROM